2018
DOI: 10.1111/apa.14468
|View full text |Cite
|
Sign up to set email alerts
|

Screening for coeliac disease in children

Abstract: There is moderate evidence that screening certain at-risk groups for coeliac disease could be beneficial, but more studies in different settings are needed before large-scale population screening can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 65 publications
0
25
1
2
Order By: Relevance
“…Thus, it can be associated with CD neurological diseases, osteoporosis, T-cell lymphoma, as well as other autoimmune diseases, such as type I diabetes, tiroiditis, and Addison's disease [5]. Recent studies demonstrate that this initially considered rare disease is relatively common, affecting around 1-3% of the general population in both Europe and North America [6][7][8]. The genetic component of CD is associated with specific class II Major Histocompatibility Complex (MHC) alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be associated with CD neurological diseases, osteoporosis, T-cell lymphoma, as well as other autoimmune diseases, such as type I diabetes, tiroiditis, and Addison's disease [5]. Recent studies demonstrate that this initially considered rare disease is relatively common, affecting around 1-3% of the general population in both Europe and North America [6][7][8]. The genetic component of CD is associated with specific class II Major Histocompatibility Complex (MHC) alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the need to estimate the benefits and the economic aspects of CD screening was emphasised. 3 The aim of the present prospective study was to evaluate diag- Seventy tests showed no line. In this group, none had IgA deficiency and none was diagnosed as having CD (Figure 1).…”
mentioning
confidence: 98%
“…In addition, there is increased risk of autoimmune disorders related directly to duration of exposure to gluten in CD. 129 Evidence about the risks of long-term severe complications in unrecognised CD is controversial 130 with some reports suggesting that the risks of malignancy, bone demineralisation and infertility may be less than previously thought. 131 Regular follow-up is essential once diagnosis is established.…”
Section: Management and Follow Upmentioning
confidence: 99%